Research Note on Online Learning in India – Issues and Challenges - Arun Kumar, A. (Prabandhan: Indian Journal of Management, 2021)
The research note focused on understanding the online mode of learning in India. The sudden outbreak of Covid-19 during 2020 transformed the traditional teaching into an online learning process. The pandemic has shown that it is important for the Indian education system to be prepared to face such challenges in the future as well. The research note was prepared based on secondary sources of existing literature on online learning. From the research, some key issues and challenges that the Indian education system is facing in the online mode of teaching were identified. Some of which include student enrollment, quality, infrastructure, technical and privacy issues, research and innovation, outreach and accessibility, and technical knowledge of teachers. With the emerging new normalcy, this research note focused on analyzing the perspectives of online education in India, and it could be a factor in understanding and contributing to thereof in decision making. The note also made its point that by implementing the suggestions provided, the Indian education system will be prepared to face any such situations in the future as well.